Immunosuppressive Activity of Size-Controlled PEG-PLGA Nanoparticles Containing Encapsulated Cyclosporine A. (29th March 2012) - Tang, Li; Azzi, Jamil; Kwon, Mincheol; Mounayar, Marwan; Tong, Rong; Yin, Qian; Moore, Robert; Skartsis, Nikolaos; Fan, Timothy M.; Abdi, Reza; Cheng, Jianjun
Abstract : We encapsulated cyclosporine A (CsA) in poly(ethylene glycol)- b -poly(d, l -lactide-co-glycolide) (PEG-PLGA) nanoparticles (NPs) by nanoprecipitation of CsA and PEG-PLGA. The resulting CsA/PEG-PLGA-NPs were <100 nm in diameter with a narrow particle size distribution. The NP size could be controlled by tuning the polymer concentration, solvent, or water/solvent ratio during formulation. The PEGylated NPs maintained non-aggregated in salt solution. Solid NPs lyoprotected with bovine serum albumin were prepared for the convenience of storage and transportation. The release kinetics of CsA (55.6% released on Day 1) showed potential for maintaining therapeutic CsA concentrations in vivo . In T-cell assays, both free CsA and CsA/PEG-PLGA-NPs suppressed T-cell proliferation and production of inflammatory cytokines dose dependently. In a mixed lymphocyte reaction assay, the IC50 values for free CsA and CsA/PEG-PLGA-NPs were found to be 30 and 35 ng/mL, respectively. This nanoparticulate CsA delivery technology constitutes a strong basis for future targeted delivery of immunosuppressive drugs with improved efficiency and potentially reduced toxicity.